2002
DOI: 10.1113/jphysiol.2002.026120
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction in the rat impairs resistance artery but not conduit artery function in pregnant offspring

Abstract: Dietary protein restriction during gestation has been shown to produce vascular dysfunction in pregnant rats and hypertension in their offspring. However, no studies have to date examined the effects of such 'programming' on the vascular function of female offspring when they in turn become pregnant. We have therefore studied isolated conduit and resistance artery function from pregnant female offspring of control (C, 18 % casein) and protein-restricted (PR, 9 % casein) pregnant dams. There were no differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 45 publications
9
74
2
Order By: Relevance
“…We also found that AChinduced relaxation, but not PE-induced contraction, was lower in the PR group. Similar results have beene reported by Torrens et al, 18) although Sathishkumar et al 19) have reported that prenatal protein restriction increased the expression of the vascular angiotensin II type 1 receptor and the angiotensin II-induced vasoconstriction. These results indicate that a protein restriction in pregnant rats affected the vascular reactivity of their offspring.…”
Section: Discussionsupporting
confidence: 87%
“…We also found that AChinduced relaxation, but not PE-induced contraction, was lower in the PR group. Similar results have beene reported by Torrens et al, 18) although Sathishkumar et al 19) have reported that prenatal protein restriction increased the expression of the vascular angiotensin II type 1 receptor and the angiotensin II-induced vasoconstriction. These results indicate that a protein restriction in pregnant rats affected the vascular reactivity of their offspring.…”
Section: Discussionsupporting
confidence: 87%
“…These human studies are strongly supported by animal experiments showing that a severe but balanced limitation of fetal substrate supply retards fetal growth and induces CV dysfunction and hypertension [7,8,9,10]. The hypothesis of developmental origins of disease proposes that maternal undernutrition causes permanent changes in structure and function of tissues and organs, resulting in CV and related disorders in the offspring [11, 12].…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies on dietary restriction produced variable results on birth weight. In some investigations, birth weight was reduced [34, 35], in others unchanged [7, 10, 14, 36] and in some even increased [37]. The discrepancies may be due to factorsthat may alter response of the mother and fetus to nutrientrestriction such as strain, maternal age and differencesin the diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding a PR diet to pregnant rats in the F 0 generation resulted in elevated blood pressure and endothelial dysfunction (Torrens et al, 2003) in both the F 1 and F 2 generations, despite normal nutrition during pregnancy in the F 1 generation. Hypomethylation of the hepatic GR and PPAR␣ promoters was also observed in both the F 1 and F 2 male offspring (Burdge et al, 2007b), suggesting that transmission of a phenotype induced in the F 1 generation to the F 2 generation may involve preservation of induced changes in the methylation of specific genes.…”
Section: Transgenerational Transmission Of Altered Epigenetic Gene Rementioning
confidence: 99%